Validation of Global Self-Rated Health and Happiness Measures Among Older People in the Yilan Study, Taiwan - Yen-Huai Lin; Yen-Huai Lin; Hsi-Chung Chen; Nai-Wei Hsu; Nai-Wei Hsu; Nai-Wei Hsu; Nai-Wei Hsu; Pesus Chou (Frontiers Media S.A., 2020)
Background: Single-item measures of physical and mental health are feasible for older adults, but their validity for that age group is unclear. This study tested validity of a global self-rated health and a global self-rated happiness measure in a large sample of community-dwelling older adults in Taiwan.Methods: A cross-sectional sample of 3,982 men and women aged 65 or older in Yilan, Taiwan, provided data on global self-rated health and happiness using 100-point numerical scales. The Physical Component Summary of the 12-Item Short Form Health Survey (version 2) and the Groningen Activity Restriction Scale were used to test the validity of the self-rated health item. The Mental Component of that 12-item scale and the Hospital Anxiety and Depression Scale were validators regarding the self-rated happiness item. Criterion validity was tested using the 12-Item Short Form Health Survey (version 2).Results: The correlations between the self-rated health and happiness measures and the 12-Item Short Form Health Survey (version 2) validators were positive and statistically significant, supporting convergent validity. Sufficient divergent validity was demonstrated through the negative and significant relationship between the self-rated health item and the Groningen Activity Restriction Scale scores and the negative and significant relationship between the self-rated happiness item and the Hospital Anxiety and Depression Scale. Optimal cut-off scores for physical and mental health states depended on age and gender.Conclusion: The global self-rated health and happiness measures were validated. Cut-off scores for evaluating older adults' physical and mental health should be age- and gender-specific.